Provenance study of the Xining loess in the Northeastern Tibetan Plateau, China - LI Zongyao; SHENG Mei; JIANG Kai; YI Shiyu; WANG Xisheng (Dizhi lixue xuebao, 2022)
Single-grain U-Pb dating of detrital zircons is regarded as an efficient and effective technique to differentiate the contribution of discrete sources. However, its application to the extensive Chinese Loess Plateau (CLP) yields rather complex information in provenance discrimination. The Xining loess was deposited in the Northeastern Tibetan Plateau (NETP), and the detrital zircon U-Pb chronology study can not only obtain provenance information but also provide an important basis to discuss the contribution of the detrital materials from the Northern Tibetan Plateau (NTP) to the CLP. Results of the detrital zircon morphology suggest that zircons may have undergone intense physical weathering and multiple recirculations, and may also indicate the high complexity of the source. Detrital zircon U-Pb age results from different sedimentary layers of the Xining loess reveal there are no obvious temporal variations in the provenance of the Xining loess since ~1.3 Ma and materials may ultimately be eroded from the NTP and the Central Asian Orogenic Belt (CAOB), although the relative contribution of detritus from the two sources may slightly vary through time. The U-Pb age spectra of the Xining loess are highly similar to that of typical loess sites in the western-central CLP, suggesting that the provenance areas of the CLP and the Xining loess may be largely consistent, but the possibility of a small difference of provenance cannot be ruled out.